Metabolome-wide association study of occupational exposure to benzene. (4th October 2021) - Rothman, Nathaniel; Vermeulen, Roel; Zhang, Luoping; Hu, Wei; Yin, Songnian; Rappaport, Stephen M; Smith, Martyn T; Jones, Dean P; Rahman, Mohammad; Lan, Qing; Walker, Douglas I
Abstract: Benzene is a recognized hematotoxin and leukemogen; however, its mechanism of action in humans remain unclear. To provide insight into the processes underlying benzene hematotoxicity, we performed high-resolution metabolomic profiling of plasma collected from a cross-sectional study of 33 healthy workers exposed to benzene (median 8-h time-weighted average exposure; 20 ppma ), and 25 unexposed controls in Shanghai, China. Metabolic features associated with benzene were identified using a metabolome-wide association study (MWAS) that tested for the relationship between feature intensity and benzene exposure. MWAS identified 478 mass spectral features associated with benzene exposure at false discovery rate < 20%. Comparison to a list of 13 known benzene metabolites and metabolites predicted using a multi-component biotransformation algorithm showed five metabolites were detected, which included the known metabolites phenol and benzene diolepoxide. Metabolic pathway enrichment identified 41 pathways associated with benzene exposure, with altered pathways including carnitine shuttle, fatty acid metabolism, sulfur amino acid metabolism, glycolysis, gluconeogenesis and branched chain amino acid metabolism. These results suggest disruption to fatty acid uptake, energy metabolism and increased oxidative stress, and point towards pathways related to mitochondrial dysfunction, which has previously been linked to benzene exposure in animal models and human studies. Taken together, these results suggest benzene exposure is associated with disruption of mitochondrial pathways, and provide promising, systems biology biomarkers for risk assessment of benzene-induced hematotoxicity in humans. Abstract : Untargeted metabolomic profiling of workers exposed to benzene and controls identified systemic alterations in pathways linked to mitochondrial dysfunction and hematopoietic stem cells. Results from this study provide new insight into biological changes underlying benzene-induced hematotoxicity.